Temporary stays with housed family and friends among older adults experiencing homelessness: Qualitative findings from the HOPE HOME study. (May 2022) - Knight, Kelly R; Weiser, Jeremy; Handley, Margaret A; Olsen, Pamela; Weeks, John; Kushel, Margot
Background: The proportion of adults age 50 and older experiencing homelessness is growing. People at risk for homelessness may stay with family and friends during homelessness episodes. Moving in with housed family and friends is a strategy used to exit homelessness. Little is known about these stays with family and friends. This study examined the motivations for and challenges of older adults experiencing homelessness staying with or moving in with family or friends. Methods: We purposively sampled 46 participants from the HOPE HOME study, a cohort of 350 community-recruited adults experiencing homelessness age ≥50 in Oakland, CA. Inclusion criteria included having stayed with housed family/friends for ≥1 nights in the prior 6 months. We sampled 19 family/friends who had hosted participants experiencing homelessness. We conducted separate, semi-structured interviews, summarized, memoed and coded data consistent using a grounded theory approach. Results: Older adults experiencing homelessness reported primarily temporary stays. Motivations for stays on the part of participants included a need for environmental, physical, and emotional respite from homelessness. Both individuals experiencing homelessness and hosts cited the mutual benefits of stays. Barriers to stays included feelings of shame, concerns about burdening the hosts, and interpersonal conflicts between older adults experiencing homelessness and host participants. Conclusions: There are potential opportunities and concerns surrounding temporary stays between older adults experiencing homelessness and their family or friends. Policy solutions should support the potential mutual benefits of temporary stays, while addressing interpersonal barriers to strengthen kinship and friendship networks and mediate the negative impacts of homelessness.